2004
DOI: 10.1094/cchem.2004.81.5.633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Secondary Structures of Heated Egg White Protein on the Binding Between Prime Starch and Tailings Fractions in Fresh Wheat Flour

Abstract: Cereal Chem. 81(5):633-636Dried egg white protein was heated at 120°C for 1 hr, added to a fresh wheat flour (protein 8.6%), and the protein and wheat flour were subjected to acetic acid (pH 3.5) fractionation. The results showed that egg white protein increased the binding between prime starch (PS) and tailings (T) fractions in wheat flour. Several conditions for heating of egg white protein were examined to determine 1) the effect of the amount of water added to the protein before heating; 2) the effect of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 10 publications
(15 reference statements)
1
17
0
Order By: Relevance
“…The changes in secondary structure of CMP gels and CMP solutions indicated that α-helix gradually converted into β-sheet during CMP gel formation. The same trend was found in heating egg white protein (Seguchi et al, 2004). Hu, Xu, Gong, and Kuang (2005) also found an apparent convert of photosystem I in which the α-helix is converted to β-sheet during 60°C to 80°C.…”
Section: Secondary Structuresupporting
confidence: 73%
“…The changes in secondary structure of CMP gels and CMP solutions indicated that α-helix gradually converted into β-sheet during CMP gel formation. The same trend was found in heating egg white protein (Seguchi et al, 2004). Hu, Xu, Gong, and Kuang (2005) also found an apparent convert of photosystem I in which the α-helix is converted to β-sheet during 60°C to 80°C.…”
Section: Secondary Structuresupporting
confidence: 73%
“…Changes in the amide I patterns can be used to predict protein secondary structure [27,28] (Fig. 5).…”
Section: Protein Amide I and Amide Ii And A-helix Andmentioning
confidence: 99%
“…Any temperature change in the environment of the protein which can influence the non-covalent interactions involved in the structure may lead to an alteration of the protein internal structures [10] . Recently research showed that heat processing affected protein moleclualr structures [10] and changed the protein α-helix to β-sheet ratio [10,11] . These changes affected nutritive quality and availability [12] .…”
Section: Introductionmentioning
confidence: 99%